ORIGINAL PAPER Transcatheter closure of secundum atrial septal defects in adults - Demkow, Marcin; Rużyłło, Witold; Jakubowska, Ewa; Konka, Marek; Kępka, Cezary; Wilczyński, Janusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2005)
Aim: To determine safety, immediate and long-term results of transcatheter closure of moderate and large secundum atrial septal defects in adults with the Amplatzer septal occluder. Methods: A prospective study in 280 consecutive patients (200 female) aged 16-76 years (42±18) included between November 1997 and May 2005. The procedures were performed under general anaesthesia to allow continuous transoesophageal echocardiographic monitoring. Results: Two hundred and sixty nine patients (96.1%) underwent successful device implantation. In these patients flow ratios of 1.4-8.5 (2.9±1.7) were calculated on 50% oxygen. The defects were: centrally placed (n=109), antero-superior with partial or total deficiency of the aortic rim (n=160) and multiple (n=18). They were 4-36 mm (18±5.2) on echocardiography and 6-36 mm (21±8) when balloon-sized. Devices of 6-40 mm (24±7.1) were implanted. Patients were followed for one month (all 269 patients), 6 months (251/269) and 12 months (219/269). Forty seven patients were followed for more than 5 years. Complete closure was achieved in 96.7% of patients, with trivial or small residual shunts related to insignificant additional defects in the remaining patients. Periprocedural complications were observed in single patients and included: cardiac tamponade treated surgically, periprocedural and postprocedural device embolization and bronchial bleeding. Among 13.5% (22 patients) of the first 163 patients treated with aspirin only post-procedure transient neurological symptoms were observed within 6 months after device implantation and were not observed after thienopyridine was added to the postprocedural protocol. Conclusion: Transvenous closure of secundum atrial septal defects with the Amplatzer septal occluder in adults is safe and effective. Moderate and large defects with complex anatomy can be closed with almost 100% early complete occlusion rate. Thienopyridine with aspirin is required within a 6-month postimplantation period. Transcatheter closure of secundum atrial septal defects with the Amplatzer septal occluder may become an alternative treatment to surgery for selected patients.